The Sexual Motivation of Male Rats as a Tool in Animal Models of Human Health Disorders - Bialy, Michal; Bogacki-Rychlik, Wiktor; Przybylski, Jacek; Zera, Tymoteusz (Frontiers in Behavioral Neuroscience, 2019)
Normal or dysfunctional sexual behavior seems to be an important indicator of health or disease. Many health disorders in male patients affect sexual activity by directly causing erectile dysfunction, affecting sexual motivation, or both. Clinical evidence indicates that many diseases strongly disrupt sexual motivation and sexual performance in patients with depression, addiction, diabetes mellitus and other metabolic disturbances with obesity and diet-related factors, kidney and liver failure, circadian rhythm disorders, sleep disturbances including obstructive sleep apnea syndrome, developmental and hormonal disorders, brain damages, cardiovascular diseases and peripheral neuropathies. Preclinical studies of these conditions often require appropriate experimental paradigms, including animal models. Male sexual behavior and motivation have been intensively investigated over the last 80 years in animal rat model. The sexual motivation can be examined using such parameters as: anticipatory behavior and 50-kHz ultrasonic vocalizations reflecting the emotional state of rats, initiation of copulation, efficiency of copulation, or techniques of classical (pavlovian) and instrumental conditioning. In the review we analyze behavioral parameters describing sexual motivation and sexual performance of male rats in the context of animal experimental models of human health disorders. Based on analysis of parameters describing heterogeneous and complex structure of sexual behavior in laboratory rodents, we propose an approach that is useful in delineating distinct mechanisms affecting sexual motivation and sexual performance in selected disease states and efficacy of therapy in preclinical investigations.